Tumor-Infiltrating Lymphocyte Therapy: Addressing Prevailing Questions. Issue 6 (November 2015) - Radvanyi, Laszlo G.
Abstract : Abstract: Autologous adoptive T-cell therapies have made tremendous strides over the last few years with excitement currently being generated by technologies that can reprogram T-cell specificities toward any desired antigen including chimeric antigen receptors and recombinant T-cell receptors. Time will tell whether these new genetically engineered T-cell technologies will be effective as advertised, especially in solid tumors, considering the limited availability of specific antigens and the difficulty in managing the unpredictable on-target, off-tissue toxicities. However, a form of T-cell therapy that has been utilized in patients more than any other and has left a lasting mark in the field is tumor-infiltrating lymphocytes (TILs). Tumor-infiltrating lymphocyte therapy has consistently yielded durable clinical responses in selected patients with metastatic melanoma and is now being increasingly applied to treat other solid tumors, including head and neck squamous cell carcinoma, cervical cancer, breast cancer, and lung cancer. Despite its long history in the clinic and key developments over the last few decades that have augmented response rates and have made TIL manufacturing more streamlined, a number of key outstanding conceptual questions remain to be answered in the TIL therapy field. In this review, we address critical questions, including the mechanism of action of TILs and active T-cell subsets, the current need for lymphoablative preconditioning, predictive biomarkers, the role of combination therapy such as checkpoint blockade, new excitement over the recognition of mutated antigens (the "mutanome") by TILs, and issues in developing TILs for nonmelanoma indications. In each case, we will critically discuss the main issues and concerns and how they can affect the eventual positioning of TIL therapy in the mainstream of cancer care.